Intentions of Patients with Diabetes to Participate in Regular Physical Activity: Application of the Theory of Planned Behaviour - Brigita Miežienė; Liuda Šinkariova; Rasa Jankauskienė (Lithuanian Sports University, 2018)
Background. The aim of this study is to evaluate the predictive power of affective and cognitive attitudes, perceived behavioural control, subjective norms and past behaviour for intentions to be physically active in a sample of patients with diabetes. Methods. The study included 114 patients with diabetes, 31.2% were men, 62.3% had Type 1 diabetes. Mean age of participants was 44.08 ± 19.31 years. Past physical activity behaviour was measured using physical activity scale from Summary of Diabetes Self-Care Activities (SDSCA) (Cronbach alpha .62) (Toobert, Hamsted, & Glasgow, 2000). Variables within Theory of planet behaviour (intentions, affective and cognitive attitudes, subjective norms and perceived behavioural control) were developed based on the recommendations made by Ajzen (2006). All Theory of planet behaviour questions were scored using a 7-point Likert scale. Cronbach alphas varied from .61 to .96. Results. Perceived behavioural control and subjective norm were significant predictors of intentions (p < .05). Emotional and cognitive attitudes as well as past physical activity were not related to intentions to exercise (p > .05). Conclusions.  Enhancing  self-efficacy  and  ability  to  control  the  disease  as  well  as  strengthening  positive relationships of patients with members of the team involved in the treatment, whose attitudes are regarded, should be considered developing interventions aimed at increasing the motivation of patients with diabetes to regularly practice  physical activities. Keywords: health behaviour, motivation, theory.